Beyond continuity: analysis of the effects of the first Trio Presidency on Policy Coherence for Development - Vieira, Alena (2012)
The present article explores whether the first Trio Presidency of the Council of Ministers of the European Union (EU), composed of Germany, Portugal and Slovenia, lived up to the goal of ensuring greater continuity and sustainability in managing the Council's work. Focusing on the Trio's performance in promoting the principle of Policy Coherence for Development (PCD) in EU global action, the article explores patterns of cooperation established by the first Trio alongside the traditional roles of the rotating presidency, as the manager, provider of political initiative, broker, and representative of the Council and member states. The contribution demonstrates the emergence of a distinctive cooperation pattern among Germany, Portugal, and Slovenia, which we refer to as, Trio effects.. While such effects were established in all presidency functions with the exception of EU external representation, the Trio effects in exerting management functions contributed most in having more continuity in the promotion of the PCD. Taking into account the particular institutional and procedural context in which the Trio operated, the contribution draws lessons for the role of the Trio in the post-Lisbon external action system. Along with the review of official policy documents and secondary sources, this contribution draws on 40 anonymous semi-structured expert interviews, which were conducted by both authors between 2007 and 2009 in Brussels, Berlin, Lisbon and Ljubljana.